Analisis Mutu Antenatal Care (ANC) dan Faktor Risiko terhadap Morbiditas dan Mortalitas Preeklampsia di RSUD dr. Soetomo - Bianca Bunga Cinta Dewi; Ashon Sa'adi; Andriyanti Andriyanti (Jurnal Sehat Mandiri, 2024)
Preeclampsia is one of the causes of maternal and perinatal deaths in Indonesia, especially in East Java. This condition can increase the risk of long-term complications and potentially cause death. Preeclampsia can worsen quickly, so Antenatal Care (ANC) is needed to monitor the condition and reduce the risk of morbidity and mortality. Objective: to analyze the relationship between ANC quality and maternal risk factors with preeclampsia morbidity and mortality. Method: This research is retrospective analytical, data collection uses secondary data obtained from patient medical records. A total of 105 patients met the inclusion criteria, namely a diagnosis of preeclampsia and a gestational age of 2023 weeks and the exclusion criteria were incomplete medical records. Research data was analyzed using the chi-square test with a level of significance (α=0.05). Results: Preeclampsia morbidity and mortality were significantly associated with BMI (P=0.006), while morbidity alone was associated with health services (P=0.001), parity (P=0.045), education (P=0.006), and type of preeclampsia (P= 0.007). Factors that were not associated with mortality were age (P=0.704), occupation (P=0.639), proteinuria levels (P=0.411), and ANC frequency (P=0.565). Conclusion: the quality of ANC services influences the incidence of preeclampsia morbidity, along with the risk factors of BMI, parity, education, and type of preeclampsia. Early identification of risk factors and improving the quality of ANC services are important for appropriate management and prevention of mortality.